In vitro Phytoextraction Capacity of Blackberry for Copper and Zinc - ERTURK, UMRAN; YERLIKAYA, CEMILE; SIVRITEPE, NURAY (Asian Journal of Chemistry, 2010)
In vitro propagated three-node shoots of blackberry cv. Chester Thornless were subjected to differen concentrations of CuSO4.5H2O (control, 50, 100 and 150 ppm) and ZnSO4.7H2O (control, 50, 100, 200 ppm) in ¼ strength MS medium, supplemented with 0.5 mg L-1 BAP, 30 g L-1 sucrose and 7 g L-1 agar, for 4 weeks. Excess levels of Cu on the growing media reduced dry biomass production of explants. In contrast to Cu treatments, dry biomass production was enhanced increasing Zn level up to 50 ppm in the growth medium. Moreover, relative growth rates of explants were not modified by 100 and 200 ppm Zn treatments. The relative chlorophyll content of leaves tended to decrease in blackberry with increasing supply of Cu and Zn. Thus, the predominant symptom appeared in metal treated explants was chlorosis. Significant changes were observed in mineral composition of the explants, however, concentrations were generally above mineral deficiency levels. The above-ground biomass of the explants exposed to different levels of Cu accumulated 498.5-1726.1 mg kg-1 in dry matter Cu and the levels were about 54-186 times higher than those of the control. Similarly, Zn content in above-ground biomass of explants treated with 50, 100 and 200 ppm Zn increased almost 10, 14 and 18 times compared with those of the non-treated ones. Based on these preliminary results, the possible usefulness of blackberry for phytoremediation technologies is discussed.